Extreme diagenesis in the Late Pleistocene stratigraphic sequence of Grotta Guattari (central Italy) and its impact on the archaeological record. (15th December 2022) - Cremaschi, M.; Nicosia, C.; Favero, M.
Abstract: Grotta Guattari is a key cave site for Mediterranean prehistory. It is where a perfectly preserved paleo-surface, littered with bones and containing a Neandertal cranium, was exposed in 1939. Recent research, moreover, has yielded even more Neandertal remains in a side chamber that had remained unexplored. This paper gives an account of the stratigraphic sequence of the atrial portion of Grotta Guattari described in 1989 along the walls of the 1939 to 1950 excavation trenches. This key sequence, capable of elucidating the sequence of events recorded in Grotta Guattari, remained until now unstudied. The stratigraphy represents the interval between ca 125 ky BP (Marine Isotope Stage – hereafter, MIS – 5.5 or Tyrrhenian transgressive cycle) and ca 50 ky BP (MIS 3). Grain size, chemical, and heavy mineral analyses were coupled with the micromorphological study of thin sections, corroborated by SEM/EDS chemical determinations and XRD analyses. The presence of secondary Ca–Al and Ca–Fe phosphates, formed in response to the weathering of guano, indicates that part of the archaeological record (bones and ash) has weathered away. Weathering was so intense that also the more unstable mineral species, especially augite, disappeared from the heavy mineral assemblage. The differential preservation of the archaeological record shall therefore be taken in consideration when interpreting in behavioural terms old and new excavation data. Highlights: Grotta Guattari is a key cave site for Mediterranean prehistory, famous for the retrieval of a Neandertal cranium in 1939. We present the results of analyses done on a stratigraphic sequence that was described in 1989 in the atrial portion of the cave and that was never published before. Secondary Ca–Al and Ca–Fe phosphates, derived from the weathering of guano, indicate that bones did not survive in some stratigraphic units that, nevertheless, contained lithics. The disappearance of bone and possibly ash constitute a potential bias in the interpretation of the cave stratigraphy in behavioural terms. The extreme diagenesis that implied secondary Ca–Al and Ca–Fe phosphates also affected the heavy mineral assemblage, with the disappearance of unstable minerals (especially augite).